Hubungan Keterlibatan Masyarakat dan Pengelolaan Wisata Bahari di Kawasan Pantai Tanjung Luar Kabupaten Lombok Timur - Dien Qibty Novia Annisa'a; Syech Idrus; Erri Supriyadi (PENTAHELIX: Jurnal Ilmiah Pengabdian Pariwisata, 2023)
This study aims to establish the relationship between community involvement and the management of marine tourism at Tanjung Luar Beach in East Lombok District. Additionally, it seeks to quantify the extent of community participation in the management of marine tourism in this coastal area. The research design adopts a quantitative approach, with data collected through observation, surveys, and documentation from a sample of 90 respondents. The study reveals a statistically significant positive relationship between community involvement and the effective management of marine tourism at Tanjung Luar Beach, indicated by a correlation coefficient of 0.431. This moderate coefficient, falling within the interval range of 0.40 to 0.431, highlights the pivotal role of community engagement in promoting the sustainable growth of marine tourism in this picturesque destination.